What I say : conversations that improve the physician-patient relationship - Osher, Robert H.; Parker, Jack S., 1986- (SLACK Incorporated, 2019)
What I Say: Conversations that Improve the Physician-Patient Relationship is designed to help cataract surgeons to hone their verbal interactions to be as sharp as their surgical skills. Muddled, clumsy, or impromptu explanations diminish the doctor-patient relationship and could prevent patients from receiving the surgery they need or appreciating the results they get.